The cultural capital of migrant children from United States in localities of Tlaxcala - Vázquez Vázquez, José Dionicio (Universidad Autónoma del Estado de México, 2020)
In this article features of the cultural capital of children who attend basic education, from the United States accompanied by their relatives, who arrive in San Simeón Xipetzingo and San Francisco Tetlanohcan, Tlaxcala, are disclosed. Cultural capital includes the family inculcation of migrant children, the use of free time, extra class activities and their application in school subjects and the social mobility of parents, as part of social and cultural heritage. The teacher's role is also important, since his experience shows some understanding towards the returned migrant child, in a school context where he puts into practice his cultural capital in a state incorporated in the cultural capital in an institutionalized state; that is, the school. The main findings show that migrant children move their cultural capitals from their homes to school.